RESULTS OF COMPLEX TREATMENT OF MAXILLOFACIAL HEMANGIOMAS IN CHILDREN - Tkachenko, P.I.; Bilokon, S.O.; Lokhmatova, N.M.; Popelo, Y.V.; Dolenko, O.B.; Korotych, N.M.; Bilokon, N.P. (World of Medicine and Biology, 2022)
In recent years, the incidence of hemangiomas of the maxillofacial area in Ukrainian children has increased significantly. In order to determine the effectiveness of their comprehensive treatment, the content of 32 inpatient case histories and 47 outpatient cards of thematic children were summarized. Capillary hemangiomas were diagnosed in 20 % of cases (in 19 % in the form of wine spots). In 25 % of cases, they were independently reduced within 7–12 months. Minor tumours in volume and depth (56 % of cases) were eliminated by diathermocoagulation or local administration of small doses of prednisone. Fractional laser therapy was used to eliminate “large spots”. Cavernous hemangiomas were diagnosed in 23 % of cases. 72 % of patients were treated with diprospan in the form of four infiltrates on the periphery of the formation. In 23% of cases, percutaneous stitching of the tumour, puncture of the neoplasm was performed, followed by administering a 70 % alcohol solution into the cavities. Mixed hemangiomas (46 % of patients) were treated with anaprilin. In 33 % of patients, pyogenic granuloma was removed by radical surgery, and in 67 % – by diathermocoagulation. Upon completion of hemangioma treatment, all children underwent a course of rehabilitation measures.
Keywords: children; maxillofacial area; hemangioma; laser therapy; surgery; diprospan; anaprilin